TEACHING SPEAKING SKILL USING PICTURE SERIES: WAYS, OBSTACLES AND ATTEMPTS TO SOLVE - M. Arbain; Fitra Ramadani; Hartatya Novika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Teachers should always attempt to create an interesting and challenging English communication during the classroom of the language teaching which actively involves the students in the teaching and learning process. This article is aimed at describing the teaching technique of speaking using picture series, the use of picture series to support the teaching of speaking skill, the obstacles or unexpected possibilities generally found in the use of picture series, and attempts done to solve/minimize the problems or to anticipate the unexpected possibilities in the teaching of speaking skill. The design belongs to descriptive. Classroom observation and interview were executed to collect the data. The result showed that in teaching speaking skill using picture series, students were divided into group work or in pair, the use of picture series to support the teaching of speaking skill in classroom depended highly on supporting factors and specific criteria, the obstacles or unexpected possibilities generally found in the use of picture series in the teaching of speaking skill cover the number of picture series distributed was sometimes imbalanced, so small, unclear and uninteresting, tended to be only black and white and was not suitable with the real condition or context.